Identifying the presence of microplastics in frogs from the largest delta of the world - Mabia Hossain Shetu; Fahmida Parvin; Shafi M Tareq (Environmental Advances, 2023)
Microplastics (MPs) are ubiquitous in a freshwater, and many fishes and amphibians used to eat the plastic fragments from those water bodies by mimicking it as food. Amphibians such as frogs play an essential role in healthy wetlands ecosystem and are receiving particular attention in recent years especially because of their global decline. However, very few studies have assessed the frog's exposure to MPs. For this purpose, this study is carried out to evaluate the exposure of frogs present in different environments of Bengal delta to MPs. Twenty-seven frogs from nine different species were collected from different habitats of Bengal delta to observe the MP's abundance and then compared based on their habitat, length, and body weight. MPs were found in the gastrointestinal tract (GIT) of 90% of the frog samples, which is relatively higher, compared to other studies conducted on tadpole and frogs. The abundance of MPs was highest (19 MPs/individual) in the Asian Common Toad (Duttaphrynus melanostictus). Microscopic analysis through a stereo microscope showed that common MP particles are fiber-like (84%) and most of the MPs are colorless. Fourier Transform Infrared analysis was done to identify the possible polymers within the MPs and it showed that polyamide (PA), polystyrene (PS), acrylonitrile butadiene styrene (ABS) and vinyl ethylene-vin acetate (EVA) were the polymers found within the MPs particles. No significant relation was found between the length and weight of frogs with MPs abundance. The abundance of MPs in GIT of the frogs indicates a high exposure and ecological risk of MPs to amphibians and other animals of Bengal delta.